Synthesis of Isoxazole Moiety Containing Thieno[2,3-d]pyrimidine Derivatives and Preliminarily in vitro Anticancer Activity (Part II) - Yong, Jianping; Lu, Canzhong; Wu, Xiaoyuan (Anti-Cancer Agents in Medicinal Chemistry, 2015)
21 new structures of isoxazole-moiety-containing thieno[2,3-d]pyrimidine derivatives(3a 3u) were synthesized for the first time and characterized using IR, 1H NMR, 13C NMR, ESI-MS and elemental analysis techniques. And then their in vitro anticancer activity against lung cancer A549, colorectal HCT116 and breast cancer MCF-7 cell lines was preliminarily evaluated using the MTT method. Among them, most compounds exhibited good to excellent anticancer activity. In particular, 3g, 3j and 3n exhibited a broad spectrum and more potent anticancer activity against A549, HCT116 and MCF-7 cell lines, which can be regarded as the promising anticancer drug-candidates.
Keywords: 3-d]pyrimidine derivatives